Design and manufacture of a plastic dressing forceps using CAD/CAM technique / Zainila Salam and Samson Michael - Salam, Zainila; Michael, Samson (Faculty of Mechanical Engineering, 2001)
The evolution of plastic technology and the improvement in the quality of the plastic products changed many people opinion on plastic goods. It is more accepted now due to these changes. More and more plastic material, whether it is a recyclable or not, is being used in our daily life. Plastics are petroleum product and they cannot be used in state of raw material. Most all of them are once molten and then form to require shape by some method or other or subjected to further processing before it is delivered as commercial goods.